Análise de correspondência para analisar o impacto da pandemia COVID-19 nos municípios do estado de São Paulo de acordo com o IDHM - Paula, Amanda Vitória Alves de [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
No final do ano de 2019, a China reportou o surto de um novo vírus, nomeado de SARS-CoV-2 responsável por causar a doença COVID-19. Em pouco tempo, o vírus se espalhou por todo o mundo, infectando milhares de pessoas em um curto intervalo de tempo. Em fevereiro de 2020, o primeiro caso no Brasil foi registrado, mais precisamente no município de São Paulo, capital do Estado de São Paulo, que será a área abordada neste trabalho. Com apenas dois meses da primeira notificação, foi decretado no território paulista quarentena de 40 dias, como tentativa de contenção do vírus devido a epidemia de casos e grande ocorrência de óbitos registrados. Assim, utilizando de técnicas de análise multivariadas, mais precisamente, análise de correspondência, este trabalho mostrará se há alguma relação entre o impacto da pandemia COVID-19 e o Índice que caracteriza desenvolvimento do município a partir de três diretrizes (saúde, renda e educação), conhecido como Índice de Desenvolvimento Humano Municipal

At the end of 2019, China reported an outbreak of a new virus, named SARS-CoV-2, responsible for causing the disease COVID-19. In a short period of time, the virus spread across the world, infecting thousands of people in a short span of time. In February 2020, the first case in Brazil was registered, more precisely in the municipality of São Paulo, capital of the State of São Paulo, which will be the area addressed in this paper. With just two months of the first notification, a 40-day quarantine was decreed in the territory of São Paulo, as an attempt to contain the virus due to the epidemic of cases and the high occurrence of registered deaths. Thus, using multivariate analysis techniques, more precisely, correspondence analysis, this work will show if there is any relationship between the impact of the COVID-19 pandemic and the Index that characterizes the development of the municipality based on three guidelines (health, income and education), known as the Municipal Human Development Index.
Correspondence analysis to analyze the impact of the COVID-19 pandemic in the municipalities of the state of São Paulo according to the IDHM
Keywords: Análise de correspondência; COVID-19; IDHM; Estado de São Paulo; Correspondence analysis; Municipal human development index (HDIM); State of São Paulo